If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 7 = 5p + 9 Reorder the terms: 7 + 3p = 5p + 9 Reorder the terms: 7 + 3p = 9 + 5p Solving 7 + 3p = 9 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 7 + 3p + -5p = 9 + 5p + -5p Combine like terms: 3p + -5p = -2p 7 + -2p = 9 + 5p + -5p Combine like terms: 5p + -5p = 0 7 + -2p = 9 + 0 7 + -2p = 9 Add '-7' to each side of the equation. 7 + -7 + -2p = 9 + -7 Combine like terms: 7 + -7 = 0 0 + -2p = 9 + -7 -2p = 9 + -7 Combine like terms: 9 + -7 = 2 -2p = 2 Divide each side by '-2'. p = -1 Simplifying p = -1
| 4/3-x/5=17/15 | | f(x)=6x^2+2x+2 | | 5d-9(7-3d)= | | log(2x-1)=2 | | 20y=-16x+56 | | 3m+2m=12-m | | -18x^4-48x^2-96=0 | | 3(y+8)=2y-6y | | w+[7+(-5)]= | | x=100/15 | | (4x-y+2)*dx+(x+y+3)dy=0 | | x=103/15 | | y=15-3 | | 15=103/x | | -7x^2+7x+3=4x-1 | | 9m-19=3m+1m | | 8+16+x=160 | | x/9.4=66 | | -x^2+12-1=0 | | 7x-2/3-6x=2/15 | | f(x)=3/x^2-2x-8 | | 1/4(4p) | | 6+7+x=60 | | 4w+17=2-w | | 9(8-m)-13=-5 | | 3(1)-2(1)=6 | | 3x^2=x^2+6x+24 | | 4x-30=8+18 | | a+b*c=d | | 8m-2=-11+9m | | 3(2)-2(2)=6 | | (x)(7)=0 |